Comparison of Erection Pierhead Segmental Method With Beam Lifter and Crawler Crane From of Time and Cost : JAPEK Elevated 2 Toll Project - Erizal (Journal of World Conference (JWC), 2021)
Jalan Toll Jakarta - Cikampek Elevated 2 is an elevated toll road built to connect the JABODETABEK area and its surroundings. One of the important jobs in the construction of the JAPEK Elevated 2 toll road is the segmental pierhead erection. This final project aims to determine the comparison of the time and cost aspects of the segmental pierhead erection method using beam lifters and crawler cranes, as well as to determine what factors influence the segmental pierhead erection method. Primary and secondary data were collected, then a comparative analysis of time and costs was carried out on the beam liftter and crawler crane methods by calculating the cycle time and the performance index of the tools. Furthermore, researchers used quantitative research by distributing questionnaires to respondents, namely all employees involved in the segmental pierhead erection process in the JAPEK Elevated 2 Toll project. The results of this study indicate that the segmental pierhead erection method using a crawler crane is faster but slightly more expensive than beam lifters. Then it is known the results of the analysis using SPSS software from the beam lifter tool, there are 17 independent variables that correlate to the dependent variable and the percentage of influence of the two variables is 53.8%. Meanwhile, from the crawler crane, there are 26 independent variables which correlate with the dependent variable and the percentage of influence of the two variables is 55.5%.